Markets as 'ultimate judges' of economic policies: Angela Merkel's discourse profile during the economic crisis and the European crisis policies - Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2015)
The purpose of this article is to offer an explanation of the predominance of austerity policies in Europe based on distinct crisis narratives and their underlying market metaphors in the discourse profile of German Chancellor Angela Merkel. The methodological approach is a combined discourse and metaphor analysis of speeches and addresses of Angela Merkel in the aftermath of the crisis applying cognitive metaphor theory in combination with a corpus linguistic approach. The main finding of this article is that the dominant conceptual metaphors in Merkel's crisis narrative subordinate policy making to superior "market mechanisms", which are attributed with human and natural characteristics. I also highlight the strong moral focus of the crisis narrative of "living-beyond-ones-means", which forces austerity policies and hence offers an explanation for the prevalence of neoliberal policies in the Eurozone. Furthermore this article contributes to the study of the role of "market metaphors" for crisis narratives of influential political leaders and provides an analysis of the impact of discursive manifestations and metaphorical analogies on economic crisis policies.
Keywords: 330; Market metaphors; politico-economic discourses; financial and economic crisis; European sovereign debt crisis; cognitive metaphor theory